Energy storage device and method for making the same
By using alkali metal salt electrolyte and electrolyte with redox active organic compounds in lithium-air batteries, combined with the ion conductive film and gas diffusion tank design, the problems of passivation and hole blockage on the cathode surface of the lithium-air battery are solved, and the problem of blockage of the pores of the lithium-air battery is achieved. High power density and stability extend battery life.
Patent Information
- Application Number
- CN201910713413.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-03
- Filing Date
- 2019-08-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-08-02
AI Technical Summary
The formation of the reaction product lithium peroxide in lithium batteries leads to passivation of the cathode surface and blockage of the pores, resulting in poor power density and cycling performance, and the instability of lithium anode has not been effectively solved.
Using an anode electrolyte containing an alkali metal salt electrolyte and a cathode electrolyte with redox activity, the anode and cathode are connected through an ion conductive film, the anode and the alkali metal solution flow circulating, the cathode is connected to the gas diffusion tank, and oxidation is used. Reducing active substances such as ethyl purpurin diperchlorate and Duquinone improve electrochemical properties.
It significantly improves the operating stability and power output of the energy storage device, extends the service life, achieves high alkali metal utilization and high power density, and shows significant kinetic performance in oxygen and dry air environments.
Smart Images

Figure CN110797608B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an energy storage device, in particular to a metal-air electrochemical battery and further to a method for preparing the energy storage device. Background Art
[0002] Among various electrochemical energy storage systems, the advantage of lithium-air batteries lies in their high energy density. However, lithium-air batteries also have problems such as huge overpotential loss, low battery capacity, low cycle and power performance. These problems are mainly related to the formation of the reaction product - lithium peroxide (Li2O2), which is insulating and insoluble, so it is easy to cover and block the cathode during discharge, causing surface passivation of the cathode and slow interfacial charge transfer. So far, the discharge depth and energy efficiency of lithium-air batteries, especially the power density, have not met practical requirements.
[0003] Researchers now propose an alternative approach using a redox flow lithium-oxygen battery (RFLOB). In this battery, the oxygen reduction and oxygen release reactions occur in a gas diffusion tank connected to the battery cathode, and the electrolyte circulates between the gas diffusion tank and the cathode. During discharge, Li2O2 is generated in the gas diffusion tank. Therefore, the surface passivation and pore clogging problems of the cathode can be reduced. However, the above method still has the problem of poor cycle performance, especially the problem of unstable lithium anode still exists.
[0004] Therefore, there is still a need for an improved energy storage device, especially a lithium-air battery, to achieve a more ideal power. In addition, there is a need for an energy storage device and a preparation method with good rechargeability. Summary of the invention
[0005] The present invention provides an energy storage device, comprising:
[0006] an anode reaction chamber including an anode and an anolyte, the anolyte comprising an alkali metal salt electrolyte;
[0007] a cathode reaction chamber comprising a cathode and a catholyte, the catholyte comprising an alkali metal salt and at least one redox-active organic compound;
[0008] an ion-conducting membrane disposed between the anode and the cathode;
[0009] The anode reaction chamber is connected to a first container carrying an alkali metal solution; and the cathode reaction chamber is connected to a second container carrying a cathode electrolyte, wherein the second container has a gas inlet for injecting gas.
[0010] In one embodiment, the anolyte further comprises an alkali metal and at least one aromatic compound dissolved in an ether solvent.
[0011] In one embodiment, the alkali metal is selected from lithium, sodium or potassium.
[0012] In one embodiment, the redox-active organic compound is selected from ethyl viologen diperchlorate, 2,5-di-tert-butyl-1,4-benzoquinone or duroquinone.
[0013] In one embodiment, the catholyte comprises at least two redox-active organic compounds.
[0014] In one embodiment, the cathode electrolyte comprises ethyl viologen diperchlorate and duroquinone, and the ratio of ethyl viologen diperchlorate to duroquinone is 1:10 to 10:1.
[0015] In one embodiment, the surface of the anode is provided with an anode active material, and the anode active material comprises one or more of the following compounds: lithium, sodium, potassium, silicon, germanium, tin, germanium dioxide, tin dioxide, iron oxide, manganese tetraoxide, nickel oxide, cobalt tetraoxide, manganese oxide, titanium dioxide, tin sulfide, ferrous disulfide, manganese sulfide, cobalt sulfide, nickel sulfide, molybdenum disulfide, lithium titanate (Li4Ti5O 12 ) and lithium titanium phosphate (LiTi2(PO4)3).
[0016] In one embodiment, the anode is further provided with a solid electrolyte membrane.
[0017] In one embodiment, a nozzle is provided at the gas inlet of the second container to spray the mixture of the gas and the cathode electrolyte into the second container.
[0018] In one embodiment, at least one of the first container and the second container is replaceable.
[0019] In one embodiment, at least one of the first container and the second container is further provided with a filter to filter the solid reaction product present in the anolyte or the catholyte.
[0020] In one embodiment, the energy storage device is a lithium-air battery.
[0021] In one embodiment, the energy storage device has a power of at least 10 mW·cm 2 power density.
[0022] In another aspect, the present invention relates to a method for preparing the energy storage device, comprising:
[0023] i) a lithium ion conductive membrane is provided between the anode and the cathode;
[0024] ii) adding an anolyte comprising an alkali metal salt electrolyte to the anode reaction chamber; and
[0025] iii) introducing a catholyte comprising an alkali metal salt and at least one redox-active organic compound into the cathode reaction chamber;
[0026] to form a dual electrolyte system.
[0027] In one embodiment, the alkali metal mixture further comprises an alkali metal and at least one aromatic compound dissolved in an ether solvent.
[0028] In one embodiment, the redox-active organic compound is selected from ethyl viologen diperchlorate, 2,5-di-tert-butyl-1,4-benzoquinone or duroquinone.
[0029] In one embodiment, the cathode electrolyte comprises ethyl viologen diperchlorate and duroquinone, and the ratio of ethyl viologen diperchlorate to duroquinone is 1:10 to 10:1.
[0030] In one embodiment, the method further comprises the steps of iv) connecting the anode reaction chamber to a first container carrying an alkali metal solution; and v) connecting the cathode reaction chamber to a second container having a gas inlet for injecting gas.
[0031] In one embodiment, the anode is pre-treated with a solid electrolyte membrane.
[0032] In one embodiment, the surface of the anode is provided with an anode active material, and the anode active material comprises one or more of the following compounds: lithium, sodium, potassium, silicon, germanium, tin, germanium dioxide, tin dioxide, iron oxide, manganese tetraoxide, nickel monoxide, cobalt tetraoxide, manganese oxide, titanium dioxide, tin sulfide, ferrous disulfide, manganese sulfide, cobalt sulfide, nickel sulfide, molybdenum disulfide, lithium titanate (Li4Ti5O 12 ) and lithium titanium phosphate (LiTi2(PO4)3).
[0033] The present invention provides an efficient energy storage device with significantly enhanced operational stability and power output, and extended service life. With the help of redox-active organic compounds, the energy storage device shows significantly enhanced kinetic performance in oxygen and dry air. By repeatedly replenishing the alkali metal negative electrode material, it can operate at an alkali metal utilization rate close to 80-100%. Moreover, when supplied with oxygen and dry air respectively, the device shows unprecedented area power. The present invention can be used in large-scale energy storage devices to provide stable power in a sustainable form. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 An energy storage device according to one embodiment of the present invention is shown.
[0035] Figure 2 An energy storage device according to another embodiment of the present invention is shown.
[0036] Figure 3 CV curves of three different electrolytes with 0.1 M LiTFSI dissolved in DMSO, TEGDME, or PC are shown. The three different electrolytes are saturated with argon (Ar) or oxygen.
[0037] Figure 4 Figure 5 shows the CV curves of (A) 10 mM EV, (B) 10 mM DTBBQ, and (C) 10 mM DQ in 0.1 M LiTFSI / DMSO electrolyte in Ar atmosphere. The inset in each figure shows the scan rate (v 1 / 2 ) and peak current (i p ) between them.
[0038] Figure 5 Shown are (A) the CV curve of 3 mM ferrocene (Fc) in 0.5 M TBABF4 / ACN electrolyte for calibration of Pt ultramicroelectrode (UME); (B) the CV curve of 2 mM DTBBQ in 0.1 M LiTFSI / DMSO electrolyte using the above UME. The reference electrode is a silver wire. For the CV curve of DTBBQ, a standard Ag / Ag + Calibrate the potential of the Ag line. The scan rate is 0.01 V·s -1 In DMSO-based electrolyte, Ag / Ag + The potential relative to Li / Li + is 3.90V.
[0039] Figure 6 shows the electrochemical behavior of redox-active organic compounds. Fig. 6A Steady-state CV curves of 2 mM EV and DQ in 0.1 M LiTFSI / DMSO electrolyte measured by a Pt ultramicroelectrode. Figure 6B CV curves of different redox-active organic compounds measured in 0.1MLiTFSI / DMSO electrolyte saturated with oxygen. The reference electrode is Ag / Ag + All potentials are based on Li / Li in DMSO electrolyte + .
[0040] Figure 7The CV curves of three redox-active organic compounds (A) EV, (B) DTBBQ, and (C) DQ in 0.1 M LiTFSI / DMSO electrolyte saturated with Ar or oxygen are shown. + The potential relative to Li / Li + is 3.90V.
[0041] Figure 8 CV curves of different concentrations of EV:DQ in 0.1M LiTFSI / DMSO electrolyte in saturated Ar or oxygen are shown: (a) EV / DQ = 2mM / 10mM, (b) EV / DQ = 5mM / 10mM, (c) EV / DQ = 10mM / 10mM.
[0042] Fig. 9 Demonstrated (A) in oxygen and Li + The IR absorbance of duroquinone in three different states was calculated in the presence of: (B) the Mulliken charge of the atoms in duroquinone, (C) the Mulliken charge of the corresponding lithium semiquinone, and (D) the Mulliken charge of the lithium duroquinone superoxide formed by the interaction of the lithium semiquinone with molecular oxygen. While the effective charge of isolated DQ is (usually) zero, the semiquinone radical anion in (C) has an effective charge of -0.43e, and the partially reoxidized DQ component of the superoxide complex in (D) retains a charge of only -0.14e, while the oxygen molecule is reduced to superoxide with an effective charge of -0.43e. Consistent with the reduced Coulomb attraction, the equilibrium Li-O distance is reduced from that in the semiquinone to that in the superoxide. Added to the anion of the DQ-Li-O2-superoxide anion complex
[0043] Fig.10 In situ spectroelectrochemical FTIR measurements of DQ (a, b), EV (c, d), and EV-DQ (e, f) electrolytes at different potentials are shown. (a, c, and e) were obtained with 0.1 M LiTFSI / DMSO electrolyte saturated with oxygen. (b, d, and f) were obtained with 0.1 M LiTFSI / DMSO electrolyte bubbled with argon. The CV scan rate was 0.01 V s -1 , the baseline of FTIR spectrum is air.
[0044] Fig.11 In situ electrochemical FTIR spectra of 100 mM DQ in 1 M LiTFSI / DMSO electrolyte with saturated O2 and Ar are shown. (A) shows the CV curve of DQ saturated with O2; (B) shows the FTIR spectra collected at three different stages of the CV measurement; (C) shows the FTIR spectra collected at three different stages of the CV measurement; (D) shows the CV curve of DQ saturated with O2; (D) shows the CV curve of DQ saturated with O2; (E) shows the CV curve of DQ saturated with O2; (F) shows the CV curve of DQ saturated with O2; (F) shows the CV curve of DQ saturated with O2; (G ... -1(D-F) shows the corresponding CV curves and FTIR spectra of DQ electrolyte in Ar. The scan rate in the CV measurement was 0.1 V s -1 .
[0045] Fig.12 In situ electrochemical FTIR spectra of 100 mM EV in 1 M LiTFSI / DMSO electrolyte with saturated O2 and Ar are shown. (A) shows the CV curve of EV saturated with O2; (B) shows the FTIR spectra collected at three different stages of the CV measurement; (C) shows the FTIR spectra collected at three different stages of the CV measurement at wavenumbers between 1800 and 1550 cm -1 (D-F) shows the corresponding CV curves and FTIR spectra of EV electrolyte in Ar. The scan rate in the CV measurement was 0.1 V s -1 .
[0046] Fig.13 In situ electrochemical FTIR spectra of 100mM / 100mM EV-DQ in 1M LiTFSI / DMSO electrolyte saturated with O2 and Ar are shown. (A) shows the CV curve of EV-DQ saturated with O2; (B) shows the FTIR spectra collected at 5 different stages of CV measurement; (C) shows the FTIR spectra collected at 1800 to 1550 cm -1 (D-F) show the corresponding CV curves and FTIR spectra of EV-DQ electrolyte in Ar. The scan rate in the CV measurement was 0.1 V s -1 .
[0047] Fig.14 Shown are the voltage (dark color) and power density (light color) versus current density of the cells in the presence of 50 mM EV (A), DTBBQ (B), and DQ (C) in 1 M LiTFSI / DMSO electrolyte under O2 sparging.
[0048] Fig.15 The discharge voltage curve of 100mM DQ in 1M LiTFSI / DMSO electrolyte under O2 spray is shown. When the voltage drops to the cut-off voltage of 1.40V, the battery is discharged at a lower current density.
[0049] Fig.16 The morphology of the carbon felt in the cathode is shown before discharge (A) and after discharge of ~37 mAh (B). The electrolyte was 1 M LiTFSI / DSMO with 100 mM DQ under O2 sparging.
[0050] Fig.17 The discharge voltage curves for the device of the invention operating with a catholyte and oxygen sparge are shown.
[0051] Fig.18 The discharge voltage curves for the device of the invention operating with catholyte and dry air spray are shown.
[0052] Fig.19 The discharge voltage curves of 3 mL of 20 mM DQ and 20 mM EV in 1 M LiTFSI / DMSO electrolyte in an Ar-filled glove box are shown. The battery was charged at 2 mA cm -2 The discharge was performed to a cut-off voltage of 2.0 V. The three plateaus showed the reduction process of two redox mediators. The electron transfer number was slightly more than 1, which may be attributed to some side reactions.
[0053] Fig. 20 The morphology of carbon felt in the cathode is shown after a discharge of about 80 mAh under O2 sparging. The electrolyte is 1 M LiTFSI / DSMO with EV-DQ (0.2 M / 0.2 M).
[0054] Fig.21 Shown are the discharge curves at high current density in the presence of (A) EV-DQ (0.1 M / 0.2 M) and (B) EV-DQ (0.2 M / 0.1 M) under O2 spray. The electrolyte is 1 M LiTFSI / DSMO.
[0055] Fig. 22 The morphology of carbon felt in the cathode after discharge of about 80 mAh under O2 sparge is shown - (A and B) using 1MLiTFSI / DSMO electrolyte containing EV-DQ (0.1M / 0.2M) and (C and D) using 1M LiTFSI / DSMO electrolyte containing EV-DQ (0.2M / 0.1M).
[0056] Fig.23 The morphology of carbon cloth in a gas diffusion tank before (A) and after (B) discharging about 80 mAh under O2 sparging is shown. The electrolyte is 1 M LiTFSI / DSMO with EV-DQ (0.2 M / 0.2 M).
[0057] Fig.24 The FTIR spectra of discharge products on carbon cloth in a gas diffusion tank after discharging about 80 mAh with an electrolyte containing EV-DQ (0.2 M / 0.2 M) are shown.
[0058] Fig.25 The voltage and power density and current density curves of the device of the present invention under different working conditions are shown. The electrolyte is 1M LiTFSI / DSMO dissolved with EV-DQ (0.2M / 0.2M).
[0059] Fig.26An embodiment of an energy storage device for operating the present invention is shown: a battery system having replaceable gas diffusion tanks.
[0060] Fig. 27 The discharge voltage curve and area power of the energy storage device of the present invention are shown with three consecutive Li anode discharges at depletion. The electrolyte is 7 mL 1M LiTFSI / DSMO with EV-DQ (0.2M / 0.2M). Based on 1 electron transfer per DQ and 1 electron per EV 2+ The theoretical capacity of two electron transfers is 28.1 mAh cm -2 . DETAILED DESCRIPTION
[0061] In one aspect, the present invention provides an energy storage device, in particular an electrochemical cell, comprising an anode reaction chamber and a cathode reaction chamber, wherein the anode and the cathode are respectively arranged in the anode reaction chamber and the cathode reaction chamber, and an ion conductive membrane is placed between the anode and the cathode. The anode reaction chamber is provided with an anolyte comprising an alkali metal salt electrolyte, and the cathode reaction chamber is provided with a catholyte. The catholyte comprises an alkali metal salt and at least one redox-active organic compound. The energy storage device further comprises a first container connected to the anode reaction chamber and a second container connected to the cathode reaction chamber to respectively provide the required electrolyte circulation. The energy storage device of the present invention has high alkali metal utilization and high power density, and can be used in different applications.
[0062] Figure 1 An energy storage device according to an embodiment of the present invention is shown. The energy storage device 100 is a metal-air electrochemical cell, specifically an alkali metal-air electrochemical cell. The energy storage device 100 includes a battery cell 102, and the battery cell 102 includes an anode reaction chamber provided with an anode 104, a cathode reaction chamber provided with a cathode 106, and an ion conductive membrane 108 disposed between the anode 104 and the cathode 106. The anode 104 includes an anode end and one or more porous alkali metal anode materials, and the anode end may be made of stainless steel. The anode material includes one or more of the following compounds: lithium, sodium, potassium, silicon, germanium, tin, germanium dioxide, tin dioxide, iron oxide, manganese tetraoxide, nickel monoxide, cobalt tetraoxide, manganese oxide, titanium dioxide, tin sulfide, ferrous disulfide, manganese sulfide, cobalt sulfide, nickel sulfide, molybdenum disulfide, lithium titanate (Li4Ti5O 12 ) and lithium titanium phosphate (LiTi2(PO4)3). In the discharge mode, the anode material charges the alkali metal, and the alkali metal ions react with the cathode to perform an oxidation-reduction reaction. The alkali metal is selected from lithium, sodium, or potassium. In this embodiment, the porous alkali metal material of the anode 104 can be a porous lithium foil.
[0063] In another embodiment, the surface of the anode 104 may be provided with an anode active material, and the anode active material includes one or more of the following compounds: lithium, sodium, potassium, silicon, germanium, tin, germanium dioxide, tin dioxide, iron oxide, manganese tetraoxide, nickel oxide, cobalt tetraoxide, manganese oxide, titanium dioxide, tin sulfide, ferrous disulfide, manganese sulfide, cobalt sulfide, nickel sulfide, molybdenum disulfide, lithium titanate (Li4Ti5O 12 ) and lithium titanium phosphate (LiTi2(PO4)3).
[0064] The anode reaction chamber is fluidly connected to the first container 110 via a pipe 112. Anode electrolyte 105, also referred to as anode electrolyte, circulates between the anode reaction chamber carrying the anode 104 and the first container 110. Anode electrolyte 105 includes an alkali metal salt electrolyte.
[0065] In one embodiment, the anolyte 105 also includes an alkali metal and at least one aromatic compound soluble in an ether solvent, and the alkali metal can be selected from lithium, sodium, or potassium. The alkali metal reacts with the aromatic compound in the ether solvent to form a charge transfer complex, which has high conductivity. This anolyte is quite safe and usually has a lower redox potential. This anolyte composed of alkali metals and aromatic compounds is particularly advantageous in some embodiments. For example, when there is no anode active material on the surface of the anode 104, this anolyte can be used as an anode active material for oxidation reaction.
[0066] The ether solvent may be selected from one or more of the following: dimethoxyethane, tetraethylene glycol dimethyl ether and / or diethylene glycol dimethyl ether. The aromatic compound may be selected from: biphenyl and / or benzophenone. The anolyte of the present invention is particularly advantageous for improving the utilization of the anode metal, and the provision of the first container 110 further facilitates the replenishment of energy, such as alkali metal material or fresh anode electrolyte. As shown in the figure, the first container 110 may contain an alkali metal solution 114, and / or a solid alkali metal, which can continuously replenish the available ions for the anode, improve the utilization, and extend the service life of the device. The composition of the alkali metal solution 114 is substantially the same as that of the anolyte 105. When the anolyte 105 is composed of an alkali metal and an aromatic compound, the alkali metal solution 114 also includes a certain amount of aromatic compounds to help dissolve the alkali metal and form a charge transfer complex.
[0067] In one embodiment, the flow rate of the anolyte 105 between the anode 104 and the first container 110 is adjusted by a pump 118 disposed on the pipe 112. When the anolyte 105 passes through the first container 110, it can be mixed with the alkali metal solution 114 and transported to the anode reaction chamber through the pipe 112. It is understood that the pump 118 can be connected to a control system (not shown) to facilitate the user to monitor and adjust the flow rate. The flow rate of the anolyte 105 can be about 5-30mL / min, about 10-25mL / min, about 13-20mL / min, or about 14mL / min. The user can adjust it according to the device performance or electrolyte supply.
[0068] In addition, the porous alkali metal material of the anode 104 may be further provided with a solid electrolyte interface membrane. The solid electrolyte interface (SEI) membrane protects the porous alkali metal material from contacting the second electrolyte 120 (i.e., cathode electrolyte) at the cathode 106, thereby avoiding or reducing the risk of short circuit. This is particularly advantageous for batteries having two semi-liquid or liquid electrolyte systems.
[0069] As for the cathode 106, the cathode 106 has an end plate and a porous material, the end plate can be made of titanium, and the porous material can be carbon felt or made of other inert materials. The cathode 106 is connected to the second container 122 by a pipe 124. The cathode electrolyte 120, which can also be called a cathode electrolyte, circulates between the cathode 106 and the second container 122. The cathode electrolyte 120 includes an alkali metal salt and at least one organic compound with redox activity, and the alkali metal salt is a salt of lithium, potassium or sodium. The salt is dissolved in a solvent, and at least one organic compound with redox activity is added to form the cathode electrolyte 120. The inventors have found that adding an organic compound with redox activity to the cathode electrolyte can greatly reduce the formation of solid redox reaction products, increase the discharge rate, and reduce or slow down the passivation effect at the cathode. In addition, the organic compound with redox activity can improve the electrochemical reversal efficiency and improve the utilization of the anode material.
[0070] In one embodiment, the redox-active organic compound is selected from ethyl viologen diperchlorate, 2,5-di-tert-butyl-1,4-benzoquinone or duroquinone. The inventors have found that ethyl viologen diperchlorate and ethyl viologen diperchlorate can participate in / assist the redox reaction in the battery as redox mediators. In addition, in order to further improve the discharge rate, two or more redox-active organic compounds can be added to the cathode electrolyte 120. In a preferred embodiment, the cathode electrolyte 120 includes ethyl viologen diperchlorate and duroquinone. The inventors have found that duroquinone has excellent electrochemical reversal performance and can also generate a strong reduction current, and the combination with ethyl viologen diperchlorate can further reduce the generation of byproducts such as insoluble superoxide, thereby reducing or inhibiting the passivation of the cathode. The ratio of ethyl viologen diperchlorate to duroquinone can be about 1:10 to about 10:1, about 1:5 to about 5:1, about 1:2 to about 2:1, or about 1:1.
[0071] Further, the cathode electrolyte 120 includes a solvent selected from dimethyl sulfoxide, tetraethylene glycol dimethyl ether or propylene carbonate. In one embodiment, the solvent is dimethyl sulfoxide (DMSO), which has good stability and reaction kinetics.
[0072] The cathode electrolyte 120 circulates between the cathode 106 and the second container 122. The second container 122 may be a gas diffusion tank, which is provided with a normal pressure of 1 atm. The gas may be a normal pressure gas or a pressurized gas, and the gas enters the second container 122 from the gas source 128 through the air inlet 126, and contacts the cathode electrolyte 120 entering the second container 122 to react. Optionally, the cathode electrolyte 120 and the gas, such as pressurized oxygen, argon or dry air, are mixed before entering the second container 122, so as to facilitate subsequent spraying into the second container 122 to promote the reaction. A nozzle may be provided at the air inlet 126 to spray the mixture of the pressurized gas and the cathode electrolyte 120 into the second container, and the nozzle may increase the reaction area and accelerate the reduction speed. The gas generated during the charging process may be discharged through the air outlet 130. The air inlet 126 and the air outlet 130 may be provided with a one-way valve respectively to prevent gas backflow.
[0073] In addition, since the second container 122 is where the reduction process occurs, there is an opportunity to accumulate insoluble reaction products formed during the reduction process. In order to further reduce the impact of the reaction products, a filter element can be added to the second container 122 to filter the solid reaction products 132 present in the cathode electrolyte 120. It is understood that various materials that can effectively filter solid substances 132 in the liquid can be used. Similarly, the first container 110 can also be arranged with a filter element.
[0074] In one embodiment, the flow rate of the catholyte 120 between the cathode 106 and the second container 122 is regulated by a pump 134 disposed on the conduit 124. Like the pump 118, the pump 134 can be connected to a control system to monitor and adjust the flow rate. The flow rate of the catholyte 120 can be about 5-30 mL / min, about 10-25 mL / min, about 13-20 mL / min, or about 14 mL / min. The user can adjust it according to the device performance, gas flow rate and / or electrolyte supply.
[0075] In one embodiment, the first container 110 and the second container 122 are separated from the battery cell 102; in another embodiment, at least one of the first container 110 and the second container 122 is integrated with the battery cell 102, that is, the compartment where the first container 110 and the second container 122 can be separated is arranged near the battery cell 102. In addition, at least one of the first container 110 and the second container 122 is replaceable. The replaceable type is particularly conducive to replenishing depleted materials and can improve efficiency.
[0076] The present invention thus provides improved energy storage devices, particularly alkali metal-air electrochemical cells, such as but not limited to lithium-oxygen cells. The energy storage devices of the present invention can achieve an output power density of 10 mW·cm -2 or above, 20mW·cm -2 or above, 30mW·cm -2 or above, 40mW·cm -2 or above, 50mW·cm -2 or above, or 60mW·cm -2 The utilization of the alkali metal can be as high as at least 60%, at least 65%, at least 70%, about 75%, about 80%, about 85%, about 90%, about 95%, or about 100%.
[0077] The present invention further relates to a method for preparing the energy storage device as described above. The method comprises:
[0078] i) providing an ion conductive membrane between the anode and the cathode;
[0079] ii) adding an anolyte comprising an alkali metal salt electrolyte as described above to the anode reaction chamber; and
[0080] iii) introducing a catholyte as described above comprising an alkali metal salt and at least one redox-active organic compound into the cathode reaction chamber;
[0081] to form a dual electrolyte system.
[0082] As mentioned above, the anode electrolyte also includes an alkali metal dissolved in an ether solvent and at least one aromatic compound. The aromatic compound can be first dissolved in the ether solvent, and then the alkali metal is added and mixed. The process can be carried out at room temperature and pressure.
[0083] As previously described, the redox-active organic compound is selected from ethyl viologen diperchlorate, 2,5-di-tert-butyl-1,4-benzoquinone or duroquinone. In a preferred embodiment, the cathode electrolyte includes ethyl viologen diperchlorate and duroquinone. Duroquinone can be first dissolved in a solvent (such as DMSO) and then ethyl viologen diperchlorate is added. The ratio of ethyl viologen diperchlorate to duroquinone can be about 1:10 to about 10:1, about 1:5 to about 5:1, about 1:2 to about 2:1, or about 1:1.
[0084] In the present invention, the method further comprises the steps of iv) connecting the anode reaction chamber to a first container loaded with alkali metal; and v) connecting the cathode reaction chamber to a second container having a gas inlet for injecting gas. The first container and the second container are as described above.
[0085] In addition, the method may also include the step of pre-treating the anode, such as but not limited to:
[0086] - having a solid electrolyte membrane attached to the anode; and / or
[0087] - The surface of the anode is provided with an anode material, wherein the anode material comprises one or more of the following compounds: lithium, sodium, potassium, silicon, germanium, tin, germanium dioxide, tin dioxide, iron oxide, manganese tetraoxide, nickel monoxide, cobalt tetraoxide, manganese oxide, titanium dioxide, tin sulfide, ferrous disulfide, manganese sulfide, cobalt sulfide, nickel sulfide, molybdenum disulfide, lithium titanate (Li4Ti5O 12 ) and lithium titanium phosphate (LiTi2(PO4)3).
[0088] The embodiments set forth below further illustrate the present invention. Based on the above description and the following exemplary embodiments, the skilled person will understand how to prepare the energy storage device of the present invention and achieve the desired effect. The skilled person will also understand that these embodiments or examples are not intended to limit the present invention.
[0089] Example
[0090] Example 1a
[0091] Energy storage devices: preparation of lithium-air batteries
[0092] This embodiment mainly demonstrates the influence of cathode design on the energy storage device. Those skilled in the art can understand that when the energy storage device of the present invention is constructed as a dual electrolyte system, its performance, such as power density, etc., will be further improved.
[0093] The following reagents were used as solvents and lithium salts to prepare the electrolyte: tetraethylene glycol dimethyl ether (TEGDME, 99%, Sigma-Aldrich), dimethyl sulfoxide (DMSO, 99.9%, Sigma-Aldrich), propylene carbonate (PC, 99.7%, Sigma-Aldrich) and lithium bis(trifluoromethane) sufonimide (LiTFSI, 99.95%, Sigma-Aldrich).
[0094] The redox-active organic compound was selected from the following compounds: ethylviologen diperchlorate (EV, 98%, Sigma-Aldrich), 2,5-di-tert-butyl-1,4-benzoquinone (DTBBQ, 99%, Sigma-Aldrich) and duroquinone (DQ, 97%, Sigma-Aldrich). Before use, all the above reagents and compounds were stored in an argon-filled box to prevent them from being exposed to air.
[0095] Figure 2 A schematic diagram of this embodiment is shown. Lithium foil and carbon felt (GFD2.5EA, SGL Group) are used as anode and cathode, respectively. Celgard 2300 separator isolates the anode from the cathode. The end plates of the anode and cathode are made of stainless steel and titanium, respectively. The size of the electrode is approximately 2×2 cm 2 . Lithium foil (2×2cm 2 ) weighs about 24.0 mg. The gas diffusion tank is made of two flasks connected by glass frit. The lithium-air battery uses 7 ml of cathode electrolyte, which consists of various concentrations of ethyl viologen diperchlorate, 2,5-di-tert-butyl-1,4-benzoquinone and / or duroquinone in 1M LiTFSI-TEGDME. The gas diffusion tank has an inlet and an outlet to allow the electrolyte to enter and exit the tank. The electrolyte circulates between the battery and the tank by a peristaltic pump. A nozzle is provided at the inlet of the tank to produce electrolyte aerosol. Pressurized gas enters the gas diffusion tank through a sprayer, and the pressurized gas is oxygen or dry air.
[0096] The lithium metal as the anode was pretreated as follows: the lithium foil was pretreated in 0.5 M LiTFSI / DMSO containing 5 vol % vinylene carbonate (abbreviated as VC) for 12 h to form a solid electrolyte interface (SEI) film to avoid short circuit.
[0097] The flow rate of the pressurized gas was about 10 L / min at ambient conditions. The flow rate of the electrolyte was 14 mL / min.
[0098] Example 1b
[0099] Determining the electrochemical properties of lithium-air batteries
[0100] The inventors tested the solution for preparing the cathode electrolyte and tested the following combinations:
[0101] i) 0.1 M LiTFSI dissolved in DMSO;
[0102] ii) 0.1 M LiTFSI in TEGDME; and
[0103] iii) 0.1 M LiTFSI dissolved in PC.
[0104] By 0.1V·s -1 The cyclic voltammetry test was performed at a scan rate of Figure 3 As shown in Figure 2, it has excellent stability, reaction kinetics, and good interaction strength with lithium ions. Therefore, 10 mMEV, DTBBQ, and DQ, three redox-active organic compounds, were prepared and tested for their application in electrolytes using DMSO. The results were shown in Figure 2 at different scan rates (0.20, 0.10, 0.05, 0.02, 0.01 V·s -1 ) was used for cyclic voltammetry test. A Pt disk (3 mm in diameter) was used as the working electrode. Ag / AgNO3 (0.01 M AgNO3 in acetonitrile) and a Pt plate were used as the reference electrode and the counter electrode, respectively. Diffusion coefficient was measured using an ultramicroelectrode (UME, about 10 μm in diameter), wherein an Ag wire was used as a quasi-reference electrode during cyclic voltammetry (CV) measurement. After 30 minutes of oxygen flow, CV measurements were performed in an oxygen-saturated electrolyte. In a nitrogen box equipped with an oxygen flow channel, the battery was tested at different current densities in a constant current mode. All of the above electrochemical measurements were performed on an Autolab electrochemical workstation (Metrohm Autolab, PGSTAT302N).
[0105] The results are as follows Figure 4As shown in Figure 2, the three redox-active organic compounds EV, DTBBQ, and DQ can act as redox mediators to promote the reduction of oxygen. In particular, duroquinone (DQ) shows excellent electrochemical reversibility in argon. + ) Experience 1e - When reduced, it has a higher diffusion coefficient than the other two (e.g. Figure 5 and Table 1).
[0106] Table 1: Electrochemical properties of different redox-active organic compounds in batteries
[0107]
[0108] In the presence of oxygen, DQ exhibits the largest reduction current, thus showing excellent oxygen reduction catalytic activity. Fig. 6A and Figure 7 As shown, the quinone-based electrolyte is around 3.25 V (vs. Li / Li + ) shows a small oxidation peak, which is attributed to the oxidation of soluble superoxide species confirmed by spectroelectrochemical and computational studies. In contrast, except for the peaks at 2.90 and 2.60 V (vs. Li / Li + ) showed two consecutive reductions due to enhanced peroxide reduction, and no similar superoxide accumulation was observed in EV-based electrolytes. Therefore, it is believed that EV is beneficial to reduce superoxide and increase cycle stability. Soluble superoxide species will form insoluble peroxide substances when entering the battery core, thereby causing electrode passivation. Therefore, the present invention designs the use of two redox-active organic compounds to prepare electrolytes.
[0109] In one embodiment, different amounts of EVs were added to the DQ-based electrolyte to eliminate the formation of soluble superoxide. Figure 6B and Figure 8 As shown, the EV-DQ (10mM / 10mM) electrolyte can effectively inhibit or prevent the formation of superoxide, and the oxidation peak of superoxide completely disappears in the CV graph, while the reduction strength is still very strong.
[0110] On the other hand, soluble quinone-superoxide complex is a charge transfer complex, and the inventors used field emission scanning electron microscopy (FESEM) to determine the presence of soluble quinone-superoxide complex. The relevant images were obtained using a Zeiss Supra 40 field emission scanning electron microscope. Before FESEM measurement, the carbon felt or nickel foam was taken out of the gas diffusion tank and washed three times with dimethoxyethane (DME), and then dried in a vacuum oven at 80°C for 24 hours. The PerkinElmer Frontier MIR / FIR system performed 16 scans and collected the Fourier transform infrared (FTIR) spectrum of the solid discharge products by the attenuated total reflection (ATR) model with a nominal resolution of 2 cm -1 In situ spectroelectrochemical FTIR measurements were performed using an ATR electrochemical cell. Fig. 9 The working electrode is a platinum disk. The counter electrode and reference electrode are a platinum plate and a silver wire, respectively. There are two holes for oxygen to enter and exit. The spectrum was collected by 6 scans with a nominal resolution of 4 cm -1 The spectral range of the measurements was from 4000 to 400 cm -1 .
[0111] like Fig.10 As shown, the FTIR spectra of the electrolytes with DQ, EV, or EV-DQ were recorded at different potentials during the CV scan and specifically show the -1 Both DQ and EV show good argon reversibility in their IR spectra. In the presence of oxygen, 1680 cm -1 The peak at shows the decrease of DQ and continues to the positive potential ( Fig.10 A), DQ at 1630cm -1 The characteristic peak at DQ disappears. The corresponding semiquinone lithium and the complex formed by semiquinone lithium and oxygen ( Fig. 9 ) showed a clear blue shift in the C=O stretching vibration. Mulliken charge distribution analysis showed that the negative charge of the semiquinone component increased from -0.43e to -0.5e under the interaction between the semiquinone radical anion and the oxygen molecule. - Shrink to -0.14e - , while O2 is reduced to O 2- Superoxide anion. Effective charge is -0.43e - Therefore, there is duroquinone-lithium superoxide (DQ-Li-O2 - ) complex. The detailed in situ FTIR spectrum of the DQ-based electrolyte is shown in Fig.11The calculation method is as follows: The geometric structures of DQ, lithium semiquinone and its complex with oxygen are calculated by using dispersion-corrected DFT (DFT-D) of Dmol3. All structures are geometrically optimized using the PWC local functional with an energy tolerance of <2×10 -5 Ha, Semi-empirical dispersion correction employs the OBS formalism of Ortmann, Bechstedt, and Schmidt. Fixed points are characterized as minima by frequency analysis. The optimized geometry is further used for single-point calculations of electron energies and infrared spectra.
[0112] In contrast, EV showed identical IR spectra in the absence and presence of oxygen, implying a low affinity for reduced oxygen species. + At 1640 and 1600 cm -1 The characteristic vibration at EV appears upon reduction and reverses back to the original EV at positive potentials. 2+ Vibration ( Fig.12 Considering the absence of oxidation peaks associated with soluble superoxide in the CV curve, it is believed that superoxide species do not exist. This may be due to the fact that EV + or EV 0 It was further reduced to peroxide. In addition, the electrolyte of EV-DQ (0.1M / 0.1M) was examined in in situ FTIR measurements. No significant difference was observed in the IR spectra when the EV-DQ electrolyte was reduced in oxygen and argon, indicating that the presence of EV effectively eliminated the soluble DQ-Li-O2 - Species. Detailed in situ FTIR spectra are shown in Fig.12 and 13 shown.
[0113] Fig.14 The DQ-based electrolyte demonstrated high power performance, although the cell stopped prematurely at about 43% lithium utilization ( Fig.15 Scanning electron microscopy (SEM) analysis of the battery after depletion revealed a thick layer of fine particles ( Fig.16 ), which may be due to the DQ-Li-O2 - The direct reduction of the electrolyte causes the formation of insoluble Li2O2, which prevents the electrode from continuing to discharge. In order to eliminate the accumulation of soluble superoxide species, EV-DQ (0.2M / 0.2M) electrolyte was used. The discharge voltage curve of the cell fed with oxygen and cathode electrolyte spray is shown in Fig.17 As shown. At 15mA·cm -2 At a constant current density of , the battery continuously delivers about 70 mAh of capacitance, with an output power density of about 36 mW cm -2, while the lithium metal loaded in the anode consumes about 80%. When the current density drops to 1 mA cm -2 When the utilization rate further increased to more than 90%, it was found that the lithium foil was completely consumed ( Fig.17 When the cell was fed with dry air, the cell remained stable at about 22 mW cm -2 The lithium utilization rate is about 90% ( Fig.18 ). The EV-DQ battery was also tested in the absence of oxygen and showed a gradual 1e - Restore (EV 2+ To EV + , DQ to DQ - and EV + to EV)( Fig.19 ).
[0114] To understand the enhancement of discharge depth in EV-DQ (0.2M / 0.2M) electrolyte, the morphology of carbon felt in the cathode was examined by scanning electron microscopy after discharge, and some loosely accumulated small particles ( Fig. 20 ). As the EV / DQ ratio increases, a higher depth of discharge can be achieved. Specifically, the EV-DQ (0.2M / 0.1M) electrolyte shows a lithium Li utilization rate close to 80-100% ( Fig.21 ). Fig. 22 The SEM images show that the carbon felt surface in EV-DQ (0.2M / 0.1M) electrolyte remains clean after full discharge, which is in sharp contrast to the EV-DQ (0.1M / 0.2M) electrolyte with different ratios, where small particle deposits are present on the carbon felt surface. These observations suggest the important role of EV in eliminating soluble superoxide species, as demonstrated by in situ FTIR measurements. Moreover, EV and DQ have excellent reversibility in DMSO.
[0115] Example 1c
[0116] Other aspects
[0117] The discharge products are mainly formed in the gas diffusion tank. Fig.23 As shown, the carbon cloth placed at the bottom of the gas diffusion tank is covered with a thick substance, except for some micrometer-sized spheres deposited on the cloth. FTIR spectroscopy measurements show that the discharge products consist of a mixture of Li2O2 and Li2CO3 ( Fig.24 ). Since the discharge products can be collected naturally in the gas diffusion tank, it is possible to produce a higher value product, Li2CO3, by capturing CO2 from the air. This process occurs spontaneously when the battery is supplied with air.
[0118] The power performance of the battery of the present invention under various working conditions is as follows Fig.25 When EV-DQ (0.2M / 0.2M) electrolyte was sprayed with oxygen and dry air, the areal power of the battery reached 60 and 34 mW·cm, respectively. -2 , which is higher than the conventional electrolyte flow, revealing the effectiveness of electrolyte spray. These values are also much higher than those reported for Li-O2 battery systems (Table 2). The present invention can reduce damage to the environment and reduce costs.
[0119] Table 2. Comparison of power density of Li-O2 battery system with the battery of the present invention.
[0120]
[0121] In addition, in the battery of the present invention, continuous operation can be achieved by physically adding alkali metal when replenishing energy. Fig.26 As shown, fuel can be supplied to the cell by simply replenishing fresh lithium foil into the anode can when it is depleted. While the discharge products accumulate in the gas diffusion can, the remaining cell components, including the electrolyte and cathode, can be used uninterrupted until the gas diffusion can is full and can then simply be replaced with an empty one. Fig. 27 The voltage curve of a cell operated with three consecutive lithium feeds is shown. The cell was maintained at 10 mA cm during the first two feeds by replenishing the anode with fresh lithium foil. -2 The stable power and capacitance are about 140mAh·cm -2 However, a power drop was observed from the third feed due to the significantly increased electrolyte viscosity. This was attributed to the presence of a large number of colloidal particles of discharge products in the electrolyte, resulting in obstruction of electrolyte flow and injection. Filters may be added to further improve this.
Claims
1. An energy storage device comprising an anode reaction chamber including an anode and an anolyte, the anolyte comprising an alkali metal salt electrolyte; A cathode reaction chamber comprising a cathode and a cathode electrolyte, wherein the cathode electrolyte comprises an alkali metal salt and at least one redox-active organic compound; wherein: The redox-active organic compound is selected from ethyl viologen diperchlorate, 2,5-di-tert-butyl-1,4-benzoquinone or duroquinone; an ion-conducting membrane disposed between the anode and the cathode; The anode reaction chamber is connected to a first container containing an alkali metal solution; the cathode reaction chamber is connected to a second container containing a cathode electrolyte, the second container has a gas inlet, and a nozzle is provided at the gas inlet to spray a mixture of gas and cathode electrolyte into the second container; the gas is oxygen or dry air; At least one of the first container and the second container is further provided with a filter to filter the solid reaction product present in the anolyte or the catholyte.
2. The energy storage device according to claim 1, wherein the anode electrolyte further comprises an alkali metal and at least one aromatic compound dissolved in an ether solvent.
3. The energy storage device of claim 1, wherein the alkali metal is selected from lithium, sodium or potassium.
4. The energy storage device of claim 1, wherein the cathode electrolyte comprises at least two redox-active organic compounds.
5. The energy storage device of claim 4, wherein the cathode electrolyte comprises ethyl viologen diperchlorate and duroquinone, and the ratio of ethyl viologen diperchlorate to duroquinone is 1:10 to 10:
1.
6. The energy storage device according to claim 1, wherein the surface of the anode is attached with an anode active material, and the anode active material comprises one or more of the following compounds: lithium, sodium, potassium, silicon, germanium, tin, germanium dioxide, tin dioxide, iron oxide, manganese tetraoxide, nickel oxide, cobalt tetraoxide, manganese oxide, titanium dioxide, tin sulfide, ferrous disulfide, manganese sulfide, cobalt sulfide, nickel sulfide, molybdenum disulfide, lithium titanate and lithium titanium phosphate.
7. The energy storage device according to claim 1, wherein the anode is further attached with a solid electrolyte membrane.
8. The energy storage device of claim 1, wherein at least one of the first container and the second container is replaceable.
9. The energy storage device of claim 1, wherein the energy storage device is a lithium-air battery.
10. The energy storage device of claim 1, wherein the energy storage device has a power consumption of at least 10 mW·cm -2 power density.
11. A method for preparing an energy storage device according to any one of claims 1 to 10, comprising: i) providing an ion conductive membrane between the anode and the cathode; ii) adding an anolyte comprising an alkali metal salt electrolyte to the anode reaction chamber; and iii) introducing a catholyte comprising an alkali metal salt and at least one redox-active organic compound into the cathode reaction chamber; to form a dual electrolyte system.
12. The method of claim 11, wherein the anolyte further comprises an alkali metal and at least one aromatic compound dissolved in an ether solvent.
13. The method of claim 11, wherein the redox-active organic compound is selected from ethyl viologen diperchlorate, 2,5-di-tert-butyl-1,4-benzoquinone or duroquinone.
14. The method of claim 11, wherein the catholyte comprises ethyl viologen diperchlorate and duroquinone, the ratio of ethyl viologen diperchlorate to duroquinone being 1:10 to 10:
1.
15. The method according to claim 11, further comprising the steps of iv) connecting the anode reaction chamber to a first container carrying an alkali metal solution; and v) connecting the cathode reaction chamber to a second container having a gas inlet for injecting gas.
16. The method according to claim 11, wherein the anode is pre-treated to have a solid electrolyte membrane attached thereto.
17. The method according to claim 11, wherein the surface of the anode is attached with an anode active material, and the anode active material comprises one or more of the following compounds: lithium, sodium, potassium, silicon, germanium, tin, germanium dioxide, tin dioxide, iron oxide, manganese tetraoxide, nickel oxide, cobalt tetraoxide, manganese oxide, titanium dioxide, tin sulfide, ferrous disulfide, manganese sulfide, cobalt sulfide, nickel sulfide, molybdenum disulfide, lithium titanate and lithium titanium phosphate.
Citation Information
Patent Citations
High energy density redox flow device
CN103503201A
Redox flow battery
KR101443209B1
A battery system
WO2016024919A1
